2001
DOI: 10.4049/jimmunol.167.5.2734
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ T Cells Kill IntracellularMycobacterium tuberculosisby a Perforin and Fas/Fas Ligand-Independent Mechanism

Abstract: Cytotoxic effector phenotype and function of MHC-restricted Mycobacterium tuberculosis (MTB)-reactive CD4+ and CD8+ T lymphocytes were analyzed from healthy tuberculin skin test-positive persons. After stimulation in vitro with MTB, both CD4+ and CD8+ T cells up-regulated mRNA expression for granzyme A and B, granulysin, perforin, and CD95L (Fas ligand). mRNA levels for these molecules were greater for resting CD8+ than CD4+ T cells. After MTB stimulation, mRNA levels were similar for both T cell subsets. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 58 publications
9
138
0
3
Order By: Relevance
“…We found that CD40/ CD40L interactions enhanced the CTL activity of CD8 ϩ T cells, providing a potential mechanism for this interaction between CD4 ϩ and CD8 ϩ T cells. CD40LT greatly increased expression of perforin and granulysin, but not that of FasL, by CD8 ϩ T cells, consistent with prior reports that human CD8 ϩ T cells lyse M. tuberculosis-infected monocytes primarily through the granule exocytosis pathway, whereas apoptosis through Fas and FasL interactions plays a minor role (17). This pathway is likely to be important in immune defenses against tuberculosis as granulysin has direct antimicrobial activity against M. tuberculosis, and the combination of perforin and granulysin results in killing of intracellular M. tuberculosis (5).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found that CD40/ CD40L interactions enhanced the CTL activity of CD8 ϩ T cells, providing a potential mechanism for this interaction between CD4 ϩ and CD8 ϩ T cells. CD40LT greatly increased expression of perforin and granulysin, but not that of FasL, by CD8 ϩ T cells, consistent with prior reports that human CD8 ϩ T cells lyse M. tuberculosis-infected monocytes primarily through the granule exocytosis pathway, whereas apoptosis through Fas and FasL interactions plays a minor role (17). This pathway is likely to be important in immune defenses against tuberculosis as granulysin has direct antimicrobial activity against M. tuberculosis, and the combination of perforin and granulysin results in killing of intracellular M. tuberculosis (5).…”
Section: Discussionsupporting
confidence: 79%
“…Nonadherent cells (95% CD8 ϩ ) were then collected, washed, and stained for granulysin and perforin as described (17). Briefly, cells were permeabilized with permeabilization buffer (BD PharMingen) for 30 min on ice, then washed with cell wash buffer (BD PharMingen) and incubated with anti-granulysin mAb, DH4 (18), antiperforin mAb, ␦G9 (Kamiya Biomedical, Seattle, WA) or isotype control mouse IgG1 (BD PharMingen), for 30 min, and then washed three times with cell wash buffer.…”
Section: Immunolabeling To Detect Ctl Effector Moleculesmentioning
confidence: 99%
“…Using computer algorithms, Klein et al identified three epitopes from the Ag85 complex that were recognized by BCG-vaccinated HLA-B*3501 individuals: a) an epitope shared by Ag85ABC (Ag85 110-118 ) b) Ag85C 268-276 ; and Ag85B [204][205][206][207][208][209][210][211][212] (110). An interesting strategy for the identification of mycobacterial epitopes that are presented by human class I MHC is to use transgenic mice that express HLA-A*0201 (109).…”
Section: Respectively)mentioning
confidence: 99%
“…Another important function of CTL and NK cells is the well-established but less well-known ability to participate in the direct killing of pathogens. Both CTL and NK cells or their products kill a broad range of bacteria, parasites, and fungi (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In particular, NK cells and CTL mediate direct antifungal activity against the opportunistic fungal pathogen Cryptococcus neoformans (15)(16)(17)(18).…”
mentioning
confidence: 99%